Developing advocacy for children and young people [ current issues in research, policy and practice - Dalrymple, Jane , 1951-; Oliver, Christine M. (Jessica Kingsley Publishers, 2008)
'The role of an advocate for children is one that I perform myself which is why I have found much of the research presented in this book so interesting ... We are all on the same side battling to improve life for children who have, through no fault of their own, been handed a very bad set of cards.'. - from the Foreword by Cherie Booth QC. Advocacy for vulnerable people is increasingly becoming a part of health and social care practice, and over the past decade policy developments have contributed to a rapid development of advocacy services for children and young people. This book explores the.